John H. Wheeler papers - Wheeler, John H. (John Hill), 1806-1882.
Correspondence; diaries; writings relating to Wheeler's service as U.S. minister to Nicaragua and to Nicaragua; manuscript of the U.S. Treasury Department Yearbook, 1868, compiled by Wheeler; scrapbooks with an index; and other papers pertaining primarily to the William Walker filibuster in Central America, North Carolina history, politics, statistics, and social activities in Washington, D.C.
Microfilm edition of containers 10-13 and containers 20-22 available
Microfilm edition of containers 1-4 available
Microfilm produced from originals in the Manuscript Division.
In part, transcripts from British archives.
Historian, diplomat, and public official.
Collection material in English.
Keywords: Walker, William, -- 1824-1860.; United States. -- Department of the Treasury; Diplomatic and consular service, American -- Nicaragua; Statistics; Nicaragua -- Foreign relations -- United States; Nicaragua -- History; Nicaragua -- History -- Filibuster War, 1855-1860.; North Carolina -- History; United States -- Foreign relations -- Nicaragua; United States -- Politics and government; Washington (D.C.) -- Social life and customs; Diplomats; Historians; Public officials